3-2-1 Code It! 2020, 8th Edition - Michelle Green (Cengage Learning, 2020)
Learn the keys to successful medical coding with Green's best-selling 3-2-1 CODE IT!, 2020 EDITION. Updated every year, this complete, easy-to-use medical coding guide is written specifically for beginning coders. You find the latest updates for ICD-10-CM, ICD-10-PCS and CPT as well as HCPCS Level II coding sets, conventions, and guidelines. Focused examples, understandable language, and clearly defined terms help you master concepts, while extensive exercises and coding cases let you apply skills and prepare to earn professional coding credentials. This well-organized, intuitive approach begins with diagnosis coding before progressing to more in-depth instruction on coding procedures and services. Clear coverage introduces both ICD-10 code sets with separate, thorough chapters on inpatient and outpatient coding and separate coverage of general and specific guidelines. HCPCS level II and CPT coding are also covered in separate chapters to further ensure the coding skills you need for career success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.